Comparison and reliability assessment of CO2 quantification methods for carbonated cementitious materials - Katsuya Namiki; Kazuya Yamashita; Kazuto Tabara; Suguru Noda (Journal of CO2 Utilization)
Various CO2-absorbing concretes have been developed; however, an accurate assessment of their CO2 content is critically important. CO2 has been quantified by releasing it from concrete and measuring the sample mass loss and/or the released CO2; however, the differences between these methods remain unexplored. In this study, cementitious materials were carbonated and evaluated using five analysis methods. The presence of free water in the samples and moisture adsorption significantly affected the sample mass. Therefore, all the samples were ground and dried by heating in vacuum before analysis. Heating above 980 °C or immersion in HCl was effective for CO2 release, and non-dispersive infrared spectroscopy and coulometric titration were effective for quantifying released CO2, with measurement variance within ± 5 %. However, CO2 release using H3PO4 was insufficient, leading to an underestimation of up to 12 %. The combination of temperature-programmed desorption and non-dispersive infrared spectroscopy had the best reproducibility among the five methods and clearly showed that CO2 and H2O were released simultaneously at the moderate temperature range. This overlap causes difficulties in the popular thermogravimetric analysis which attributes the mass change below/above a threshold temperature to H2O/CO2, respectively. CO2 contents were underestimated due to the unaccounted CO2-derived mass loss for CO2-rich samples and/or high threshold temperatures while overestimated due to misincluded H2O-derived mass loss for H2O-rich samples and/or low threshold temperatures. This study presents a highly reliable approach for assessing CO2 fixation, which is essential for calculating the carbon footprints of various cementitious materials and concrete.